BEHAVIOURAL MARKERS OF THE SERVICEMAN PERSONALITY IN COURSE OF INTRAPERSONAL CONFLICT - Мельник, Я.; Беспалько, А. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
The article presents the results of the theoretical research of the nature of an intrapersonal conflict and defines the behavioral markers of the military servant, when he experiences this psychological phenomenon. The state of an intrapersonal conflict arises in the event that the circumstances of life require the individual to take such actions and conditions that are at the limit of his adaptive capabilities or exceed them. At the heart of an intrapersonal conflict is a personally significant contradiction between different needs, motives, and goals of the individual, which is displayed in the cognitive, emotional and behavioral spheres of the individual. Characteristic signs of the manifestation of an intrapersonal conflict in a military servant in the cognitive sphere are in attention, a decrease in self-esteem, an internal discrepancy between the images "I am the ideal" and "I am real", "I want" and "I can", "necessary" and "I can"; In the emotional sphere – the prevalence of negative mental states, namely asthenic mood, anxiety, tension, apathy and aggression; in the behavioral sphere - a decrease in the performance of professional activity, a decrease in the intensity and effectiveness of communication links, as well as attempts at seclusion and avoidance of interpersonal contacts. Key words: intrapersonal conflict, intrapersonal contradiction, behavioral markers, military servant.